High acceptability, feasibility and sustainability of a direct‐to‐pharmacy differentiated PrEP delivery model in public health HIV clinics in Kenya: perspectives of PrEP clients and healthcare providers - Emmah Owidi; Kenneth Ngure; Vallery Ogello; Njeri Wairimu; Lydia Etyang’; Winnie Waituika; Margaret Mwangi; Dominic Mwangi; Simon Maina; Elizabeth Irungu; Catherine Kiptinness; Nelly Mugo; et al. (Journal of the International AIDS Society, 2025)
Abstract Introduction High client opportunity costs and a burdened healthcare system limit oral pre‐exposure prophylaxis (PrEP) delivery in Kenyan public HIV clinics. We conducted a qualitative study among PrEP clients and providers to understand the acceptability, feasibility and willingness to implement a client‐centred, differentiated direct‐to‐pharmacy (DTP) PrEP refill visits intervention aimed at improving the efficiency of PrEP implementation in real‐world clinics. Methods From March 2021 to March 2022, we conducted in‐depth interviews with clients and healthcare providers participating in an individual facility pharmacy‐based PrEP delivery model for PrEP refills among clients in the continuation phase at two public HIV clinics in central Kenya. The core components of the DTP model included directed‐to‐PrEP pharmacy refill visits conducted by facility pharmacy staff and client HIV self‐testing (HIVST) while waiting for services at the pharmacy. We used semi‐structured interview guides informed by the Consolidated Framework for Implementation Research (CFIR). We analysed data using thematic content analysis and organised findings by CFIR constructs. Results We interviewed 20 PrEP clients and 20 healthcare providers. PrEP clients included 15 females and had a median age of 39 years (interquartile range [IQR]: 33–48). Providers included 13 females, had a median age of 32 years (IQR: 30–41), and included 10 HIV counsellors, 5 pharmacy and 3 clinical providers. Both providers and clients reported high satisfaction with DTP PrEP refill visits derived from improved clinic flow and quality of service. Among clients, shorter waiting times and less movement between multiple clinic rooms reduced delays, improved privacy and reduced stigma associated with visiting HIV clinics. Furthermore, shorter waiting times and infrequent clinic visits reduced loss of working hours and income among clients, motivating PrEP continuation. Providers reported improved clinic flow, reduced work burden among non‐pharmacy providers, improved knowledge and ease of implementing DTP refill visits. However, providers expressed concerns about the potential loss of roles among HIV counsellors and the shifting of workload burden to pharmacy providers. Conclusions Differentiated DTP refill visits with HIVST were highly acceptable and feasible among PrEP clients and providers. Context‐specific modifications and scale‐up of the intervention could improve the efficiency of PrEP delivery within public HIV clinics in Kenya and similar settings.